Aspectos regulatórios e conceituais das políticas tarifárias dos sistemas de transporte público urbano no Brasil - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This article presents some concepts, relevant legislation as well as a characterization model of tariff policies of public transport services in Brazil. The text also presents the main regulatory and economic variables that characterize a pricing policy, discussing the current challenges of reducing the public transport fare price that were placed by the Brazilian society in the protests of 2013. The rates of public transport have been rising year after year above inflation while the services lost demand and competitiveness. The article discusses new forms of pricing and payment for services in the light of the proposed analytical framework.
Keywords: R41; 330; mass transit; urban transportation; bus tariff; bus service funding; urban transport cost